Effectiveness of Acceptance and Commitment Therapy on Pregnancy Concerns, Stress Coping Schemas, and Interpersonal Sensitivity in Pregnant Women with Pregnancy Anxiety - Davoudi, Mandana; Pouladi Rishehri, Ali; Danesh, Esmat (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The aim of the present study was to determine the effectiveness of Acceptance and Commitment Therapy (ACT) on pregnancy concerns, stress coping schemas, and interpersonal sensitivity in pregnant women with pregnancy anxiety.Methods: The research method was quasi-experimental, utilizing a pre-test, post-test design with a control group and a two-month follow-up phase. The statistical population consisted of all pregnant women with pregnancy anxiety at Shaheed Beheshti Women's Hospital in the city of Nowshahr, who scored one standard deviation above the mean and were willing to participate in the therapy sessions. A purposive sampling method was used to calculate a sample size of 75 participants (at least 25 per group). These 75 participants were then randomly assigned to two groups of 25 each (25 in the ACT experimental group and 25 in the control group). The Parker Interpersonal Sensitivity Questionnaire (1989), Wong and colleagues’ Stress Coping Schemas (2006), and Alderdice and Lynn’s Pregnancy Concerns Questionnaire (2011) were distributed among them. As mentioned, after collecting the data from the initial sample, the data were entered into SPSS software version 26.Findings: The results showed that Acceptance and Commitment Therapy significantly reduced pregnancy concerns (F=68.93, P